Aligning Teacher Knowledge with the Science of Reading: Evidence from Structured Literacy Implementation in Elementary Classrooms - Ismail Ismail; Rahmat Rahmat; Abdul Haling; Nikita Pramudia (Universitas Muhammadiyah Enrekang, 2026)
Background. The science of reading emphasizes explicit, systematic, and cumulative early literacy instruction, yet gaps often persist between teachers’ conceptual knowledge and classroom practice, especially in rural schools. Purpose. This study examined teachers’ knowledge alignment with the science of reading, the quality of structured literacy implementation, and the relationship between both constructs. Methods. Using a quantitative correlational design, data were collected from 14 early-grade teachers in two rural public elementary schools in South Sulawesi, Indonesia. Teachers completed a science-of-reading-aligned knowledge assessment, and their instruction was observed twice using a structured literacy observation rubric. Descriptive statistics and Pearson correlations were used for analysis. Results. Teachers showed moderate overall knowledge alignment, with strengths in phonics and orthographic knowledge but weaknesses in phonological and phonemic awareness. Classroom observations also indicated moderate structured literacy implementation, marked by relatively strong explicit instruction but weaker integration of reading components and limited instructional responsiveness. A significant positive relationship was found between teacher knowledge alignment and instructional quality, especially for explicitness and systematic sequencing. Conclusion. Teacher knowledge alignment mediates the connection between evidence-based reading theory and classroom practice; therefore, stronger teacher preparation and sustained professional development are essential for improving